Procedure for modeling dynamic processes of the electromechanical shock absorber in a subway car - Liubarskyi, Borys; Lukashova, Natalia; Petrenko, Oleksandr; Yeritsyan, Bagish; Kovalchuk, Yuliia; Overianova, Liliia (Eastern-European Journal of Enterprise Technologies, 2019)
A procedure has been devised for modeling the dynamic processes in the proposed structure of an electromechanical shock absorber. Such shock absorbers can recuperate a part of the energy of oscillations into electrical energy allowing the subsequent possibility to use it by rolling stock. The procedure is based on solving the Lagrange equation for the electromechanical system. The model's features are as follows. The model takes the form of a Cauchy problem, thereby making it possible to use it when simulating the processes of shock absorber operation. Two generalized coordinates have been selected (the charge and displacement of the armature). The components of the Lagrange equation have been identified. Based on the results from magnetic field calculation and subsequent regression analysis, we have derived polynomial dependences of flux linkage derivatives for the current and linear displacement of an armature, which make it possible to identify a generalized mathematical model of the electromechanical shock absorber. The magnetic field calculations, performed by using a finite-element method, have allowed us to derive a digital model of the magnetic field of an electromechanical shock absorber. To obtain its continuous model, a regression analysis of discrete field models has been conducted. When choosing a structure for the approximating model, a possibility to analytically differentiate partial derivatives for all coordinates has been retained. Based on the results from modeling free oscillations, it was established that the maximum module value of current is 0.234 A, voltage – 52.9 V. The process of full damping of oscillations takes about 3 seconds over 4 cycles. Compared to the basic design, the amplitude of armature oscillations and its velocity dropped from 13 to 85 % over the first three cycles, indicating a greater efficiency of electromechanical shock absorber operation in comparison with a hydraulic one. The recuperated energy amounted to 3.3 J, and the scattered energy – 11.5 J.